A Study of Food Related Nutritional Deficiency in KBK Districts of Orissa - Planning Commission (Planning Commission, 2007)
Malnutrition continues to be the wide spread problem in Orissa even though there has been significant improvements in food production and advancements in science during the last fifty years. Not only that various poverty alleviation programmes had been implemented in the past to bring in overall economic improvements of the poor but also many nutrition related programmes like the Integrated Child Development Scheme (ICDS), including Supplementary Nutrition, Nutrition and Health Education, Health Care, Immunisation and Childhood Care and pre-School Education (ECCE), National and State Old Age Programme (NOAP and SOAP), Mid-day-Meal Programme (MOM), Emergency Feeding Programme etc have been launched in the State for past many years.
Planning Commission, Government of India